Rethinking the color line - Gallagher, Charles A. (McGrawHill, 2009)
Rethinking the Color Line is a user-friendly text that does not sacrifice intellectual or theoretical rigor. This anthology of current research examines contemporary issues and explores new approaches to the study of race and ethnic relations. The featured readings effectively engage students by helping them understand theories and concepts, and encourage active learning in the classroom all while providing relevance for students from all ethnic, racial, cultural, and economic backgrounds. The new fourth edition features 8 new readings as well as a new two-color design that brings attention to the "Seeing the Big Picture" and "Questions to Consider" boxes found throughout the text.